Comparative Evaluation of Functional Outcomes Following Surgical and Conservative Management of Distal Tibia Shaft Fractures: A Prospective Observational Study - Amit Saxena; Surendra Kumar Mahore; Anshul Gupta; Ashish Kumar Sriwastava; Mansi Gupta (Journal of Orthopaedic Case Reports)
Introduction: Distal tibia shaft fractures pose significant treatment challenges due to limited soft tissue coverage and suboptimal vascularity in the region. Selecting the most appropriate management strategy – whether surgical or conservative – remains a subject of ongoing debate, particularly in resource-limited settings. Materials and Methods: A prospective observational study was conducted at a tertiary care center in central India between October 2022 and April 2024, involving 70 skeletally mature patients with distal tibial shaft fractures. Patients were managed either conservatively or through surgical interventions, including intramedullary nailing (IMN), minimally invasive plate osteosynthesis (MIPO), or external fixation. Clinical outcomes were assessed at 6 weeks, 3 months, 6 months, and 12 months post-treatment using the Modified Johner and Wruhs criteria. Radiological union, weight-bearing progression, pain severity, and complication rates were also evaluated. Results: The majority of patients (92.9%) underwent surgical treatment, with IMN being the most frequently used modality (46.2%), followed by MIPO (30.8%) and external fixation (23%). Conservative management was employed in 7.1% of cases. At the 12-month follow-up, full weight-bearing was achieved in 83.3% of IMN, 80% of MIPO, and a variable proportion of external fixation patients. Radiological union with more than three cortices was observed in 90% of IMN and 75% of MIPO patients by 12 months. Overall, excellent-to-good functional outcomes were achieved in 78.6% of cases. Superficial and deep infections, as well as non-union, were more common with external fixation. Conclusion: IMN and MIPO demonstrated superior functional and radiological outcomes compared to external fixation and conservative methods. IMN, in particular, provided faster recovery with fewer complications, making it the preferred modality in appropriately selected cases.